The Influence of Job Mutation, Professional Competence, and Extrinsic Motivation on Employee Performance of PTPN IV Regional II Kebun Limau Mungkur - Siti Nurhaliza; Julianto Hutasuhut; Anggia Sari Lubis; Muhammad Rahmat (International Forum of Researchers and Lecturers, 2025)
This research is motivated by the importance of human resource management through job transfers, increasing professional competence, and extrinsic motivation to improve employee performance, especially in the plantation sector. PTPN IV Regional II Kebun Limau Mungkur is a state-owned company that prioritizes AKHLAK values in its management practices. The main objective of this study is to analyze the effect of job transfers, professional competence, and extrinsic motivation on employee performance. The research approach used is quantitative associative with multiple linear regression analysis method. The population in this study were all employees of PTPN IV Regional II Kebun Limau Mungkur totaling 125 people, with a sample of 95 respondents determined by the Slovin formula. Data collection techniques were carried out through field studies, documentation, and questionnaire distribution. Data analysis was carried out by testing validity, reliability, classical assumption tests, and multiple linear regression using the SPSS program. The results of the study showed that partially, job transfers, professional competence, and extrinsic motivation each had a positive and significant effect on employee performance. Meanwhile, simultaneously the three variables also had a significant effect on employee performance. This finding emphasizes the importance of implementing appropriate HR management policies to support company productivity and sustainability.